Design and Development of a Transceiver Device with a Power Control and Monitoring Application for Boarding House Tenants based on LoRa - RAFSYAM, YENNIWARTI; NIXON, BENNY; PUTRI, KHOMALA ERNIA; ANGELICA, MOLLIYANA TOTA; HASANI, RIFQI FUADI; NURJIHAN, SHITA FITRIA; PRASETYA, IRWAN (Institut Teknologi Nasional, Bandung, 2025)
Electricity costs in boarding rooms are often unfairly distributed because each room is charged the same amount, even though electricity usage varies. To solve this problem, a system was created to monitor each room's power usage more efficiently using Long Range (LoRa) technology. This system uses an ESP32 microcontroller, a PZEM-004T sensor, and LoRa, programmed with Arduino IDE. The sensor collects power usage data and sends it to the boarding house owner over the LoRa network, with accuracy close to 99% in three tests. The data is transmitted up to 150 meters with an RSSI of -107 dBm in non-line-of-sight (NONLOS) conditions and up to 600 meters with an RSSI of -111 dBm in line-of-sight (LOS) conditions. It is also connected to an Android app for easier power management and monitoring.